Total particulate matter, PM10, PM2.5 emissions from palm oil mill boiler - Syahirah, M. M. (Penerbit UTM Press, 2016)
Utilization of fiber and shell as boiler fuel in palm oil mill industry generates particulate emission that need to be controlled before emitting to the environment. This study investigates the particulate mass size distribution of particulate matter sampled from palm oil mills having different boiler capacities. The particulate emission was performed at the stack following US EPA Method 17 and while the particulate size distribution was determined using particle size analyzer. Results showed that the total particulate mass concentration varied between 0. 42 and 3. 77 g/Nm3 (corrected at 7% O2). The emitted particulate was mainly found in the coarse particles, with 50% cumulative size distribution ranged from 21 to 38 μm. The particulate mass concentration of PM2.5 and PM10 of the total particulate emission was varied from 0.03 to 0.30 g/Nm3 and 0. 37 to 0. 73 g/Nm3, respectively. This contributes 0. 8 to 71% and 13 to 95% of the total particulate mass concentration, respectively.